Effect of sorghum and barley-containing bread on plasma total polyphenols, antioxidant status and inflammation in healthy subjects - Hajira, Bibi; Khan, Imran (Journal of food science and technology, 2022)
The aim of this study was to investigate the effect of bread incorporated with whole-grain red sorghum and barley flours on biomarkers of oxidative stress and inflammation in humans. In a randomized cross-over study, 20 healthy subjects consumed either control bread made of all-purpose wheat flour only or bread containing 40% whole-grain red sorghum and barley flours (20% each), with a washout period of 1–2 week. The test breads were fed at breakfast after 12 h fast. Blood samples were collected at baseline (fasting) and 2 h after intake of breads. Plasma total polyphenols, total antioxidant capacity (T-AOC), superoxide dismutase (SOD) activity, thiobarbituric acid reactive substances (TBARS) and highly sensitive C-reactive protein were assessed. Compared to fasting values, the 2 h postprandial levels of plasma total polyphenols ( P = 0.001), T-AOC ( P = 0.031) and SOD activity ( P = 0.026) were significantly higher following consumption of sorghum and barley-containing bread (SBB). Moreover, net changes in plasma total polyphenols ( P = 0.001), T-AOC ( P = 0.047) and SOD activity ( P = 0.035) were significantly higher following consumption of SBB. In conclusion, bread containing whole-grain red sorghum and barely flours enhanced plasma total polyphenols and antioxidant status and hence its consumption would modulate biomarkers of cardio-metabolic health.